Prospects of using nanosilver for disinfectants in the pharmaceutical industry - Беденко, О. О.; Косоголова, Л. О.; Яблонська, К. М. (Problems of Environmental Biotechnology, 2014)
We investigated the influence of nanosilver on the proteolytic activity of Aspergillus niger at different processing modes. The largest effect of silver nanoparticles have been observed at 36 °C and treatment time – 60 min. The value of proteolytic activity in this mode was 1.3 units/g, which is 86 % less compared to the control.